Forensic Intelligence - Milne, Robert (CRC Press, 2013)
When forensic recoveries are properly processed and recorded, they are a major intelligence source for crime investigators and analysts. This volume describes how to use the evidence recovered at crime scenes for extended analysis and the dissemination of new forensic intelligence. Drawing on the author's 40 years of experience in the field, the.